2022
DOI: 10.3390/ijms232012119
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine–Paclitaxel Chemotherapy for Patients with Advanced Urothelial Cancer Refractory to Cisplatin-Based Chemotherapy: Predictive Role of PGK1 for Treatment Response to Cytotoxic Chemotherapy

Abstract: An investigation of alternatives to immune checkpoint inhibitors for advanced urothelial cancer (aUC), with biologic information, is urgently needed. Clinical data for 53 patients who received gemcitabine–paclitaxel therapy (GP) as 2nd-line chemotherapy for aUC refractory to platinum-based chemotherapy were retrospectively reviewed. The efficacy and tolerability of GP were evaluated, and the predictive value of phosphoglycerate kinase 1 (PGK1) immunostained in surgical specimens was investigated for treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Taxanes have demonstrated modest efficacy in mUC treatment [11,12]. The combination of either paclitaxel or docetaxel with gemcitabine (GT) has shown promising efficacy and tolerance in second-line of platinum-refractory setting [13,14], or as a first-line treatment [15][16][17][18]. However, all the studies on taxanes were retrospective or small-sized prospective studies; no randomised trial has directly compared GT with platinum-based chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Taxanes have demonstrated modest efficacy in mUC treatment [11,12]. The combination of either paclitaxel or docetaxel with gemcitabine (GT) has shown promising efficacy and tolerance in second-line of platinum-refractory setting [13,14], or as a first-line treatment [15][16][17][18]. However, all the studies on taxanes were retrospective or small-sized prospective studies; no randomised trial has directly compared GT with platinum-based chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, in the paper by Koguchi et al [ 6 ] the predictive value of phosphoglycerate kinase 1 (PGK1) was investigated for treatment outcomes in first- and second-line chemotherapy in patients with advanced urothelial cancer. It was observed that the non-response rates to first-line chemotherapy were significantly higher in patients with a high expression of PGK1 in the nucleus than in those with a low expression.…”
mentioning
confidence: 99%